2002
DOI: 10.1101/gr.224102
|View full text |Cite
|
Sign up to set email alerts
|

A Genome-Wide Screen for Normally Methylated Human CpG Islands That Can Identify Novel Imprinted Genes

Abstract: DNA methylation is a covalent modification of the nucleotide cytosine that is stably inherited at the dinucleotide CpG by somatic cells, and 70% of CpG dinucleotides in the genome are methylated. The exception to this pattern of methylation are CpG islands, CpG-rich sequences that are protected from methylation, and generally are thought to be methylated only on the inactive X-chromosome and in tumors, as well as differentially methylated regions (DMRs) in the vicinity of imprinted genes. To identify chromosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
121
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(128 citation statements)
references
References 46 publications
7
121
0
Order By: Relevance
“…In our study, the methylation level of chicken HSP70 promoter CpG island was detected using the MassARRAY system, and it revealed hypomethylation of this region in the control, 3-, and 6-h treatment groups in various tissues. The low level of methylation agreed with current data showing that in normal somatic cells, CpG islands are unmethylated or hypomethylated (Strichman-Almashanu et al, 2002;Song et al, 2005). The results of DNA methylation analysis indicated that regardless of tissue type, the chicken HSP70 promoter showed a similar methylation incident, meaning that the tissue-dependent expression of chicken HSP70 was not associated with the DNA methylation pattern, but interestingly, the methylation level may be negatively associated with mRNA expression because the methylation level of the control and 6-h treatment groups was slightly higher than that of the 3-h treatment group (except in liver tissue), whereas mRNA expression was higher in the 3-h treatment group, and correlation analysis showed that the methylation level was negatively associated with the mRNA level of HSP70 in leg muscle (P = 0.0124).…”
Section: Discussionsupporting
confidence: 79%
“…In our study, the methylation level of chicken HSP70 promoter CpG island was detected using the MassARRAY system, and it revealed hypomethylation of this region in the control, 3-, and 6-h treatment groups in various tissues. The low level of methylation agreed with current data showing that in normal somatic cells, CpG islands are unmethylated or hypomethylated (Strichman-Almashanu et al, 2002;Song et al, 2005). The results of DNA methylation analysis indicated that regardless of tissue type, the chicken HSP70 promoter showed a similar methylation incident, meaning that the tissue-dependent expression of chicken HSP70 was not associated with the DNA methylation pattern, but interestingly, the methylation level may be negatively associated with mRNA expression because the methylation level of the control and 6-h treatment groups was slightly higher than that of the 3-h treatment group (except in liver tissue), whereas mRNA expression was higher in the 3-h treatment group, and correlation analysis showed that the methylation level was negatively associated with the mRNA level of HSP70 in leg muscle (P = 0.0124).…”
Section: Discussionsupporting
confidence: 79%
“…There are more than 60 identified autosomal imprinted genes, about half of which are paternally repressed and half maternally repressed. Most imprinted genes that have been examined contain at least one DMR located in the 5′ promoter region or in the body of the gene itself 3 . Recently, several proteins (DNA methyltransferases, CpG methyl binding proteins, chromatin insulators) have been identified as trans-acting factors involved in the epigenetic regulation of these loci 4 .…”
Section: These Data Identify Eed As a Member Of A New Class Of Trans-mentioning
confidence: 99%
“…CpG islands (CGIs) have been identified as CpG-rich regions that are associated with ∼50% of the promoter regions in the mouse genome (Bird et al 1985;GardinerGarden and Frommer 1987). Previous genome-wide DNA methylation analyses, focusing on CGIs, have indicated that every cell and tissue type has a unique DNA methylation profile, comprising at least hundreds of T-DMRs (Ohgane et al 1998;Shiota et al 2002;Strichman-Almashanu et al 2002), and these data suggested that a methylation profile could be used to identify cell types (Shiota 2004).…”
mentioning
confidence: 99%